Toward a positive theory of public participation in government: Variations in New York City's participatory budgeting. (25th May 2021) - Shybalkina, Iuliia
Abstract: Normative research on public participation in government related to desirable amounts and modes of participation has been flourishing. However, positive research explaining variations in real‐world participation processes, while gaining momentum, is still thin and fragmented. This article aims to further the positive perspective by examining differences in participatory budgeting (PB) and the reasons for these differences in six New York City council districts based on fieldwork and secondary sources. The evidence suggests that district offices were invested in PB to gain strategic advantages, such as answering calls for political renewal, recovering from a mismanagement scandal, and signaling progressive values. Similarly, civil society organizations steered their resources toward PB only if they were interested in agenda items and in doing work with as opposed to against public officials. In the end, this study discusses implications for positive research and possible external interventions to achieve more even participation standards. Abstract in Ukrainian: Залучення громадськості до державного управління часто вивчається з «нормативної» точки зору, тобто виносяться судження про цінність залучення та його різних шляхів. «Позитивні» дослідження, які мають справу з реальними процесами залучення громадськості, набирають обертів, але ще існує багато суперечок. Ця стаття має на меті посприяти розвиткові позитивної точки зору. Для цього вона досліджує відмінності у «спільному бюджетуванні» та причини цих відмінностей у шести районах Нью‐Йорка на основі польових та вторинних даних. Факти свідчать, що лише ті райони, в яких політичні еліти зрозуміли що вони можуть отримати стратегічні переваги від спільного бюджетування, доклали зусиль до процесу. Приклади таких ситуацій включають зміни еліт, корупційні скандали, та попит на прогресивні цінності. Схожим чином, лише громадські організації які були зацікавлені у темах на порядку денному та співпраці з чиновниками приєдналися до процесу. На останок, ця стаття обговорює наслідки для позитивних досліджень та можливості зовнішнього втручання для досягнення певного стандарту залучення громадськості.